The apophatic knowledge in philosophy and theology. Emil Cioran Versus Dumitru Staniloae - Petrov, George Daniel (Technium Social Sciences Journal, 2021)
Two of the most enlightened minds of the Romanian people cross their feather quills in a subject of immeasurable depth. Both driven by the longing for God, they relate to Him from different perspectives, perspectives from which different conclusions result. One is a convinced nihilist, who cannot help but think of God, and the other an accomplished theologian, who transforms the knowledge of God into authentic living by His will. The parallel between Emil Cioran and Dumitru Staniloae on the topic of apophatic knowledge can only impress any knowledge-loving reason.